Comprimentos cromossômicos de dois cultivares de Gossypium hirsutum L. e dois ecótipos de Gossypium barbadense L. - Ferrer-Pereira, H. E.; Méndez-Natera, J. R.; Alcorcés-de-Guerra, N. C. (Acta Biológica Paranaense, 2007)
Comprimentos cromossômicos de dois cultivares de Gossypium hirsutum L. e dois ecótipos de Gossypium barbadense L.